Foreign Direct Investment in Post-Conflict Countries: The Case of Iraq’s Oil and Electricity Sectors - Hanna, Ghassan Faraj; Hammoud, Mohamad Saleh; Russo-Converso, Judith A. (International Journal of Energy Economics and Policy, 2014)
Foreign direct investment is new phenomenon to Iraq, a post conflict country with abundance of natural resources. With dominant state-controlled public sector, attracting foreign investment is an added challenge to an economy devastated by years of wars. A qualitative case study was conducted to assess determinants of foreign direct investment in Iraq’s energy sector. Data was collected from interviews with business and government subject matter experts, and a review of publically available documents. Lack of security, political instability, corruption, and inadequate government policies towards foreign direct investment as symptoms found and typically shared by other post-conflict countries. The persistence of violence was not seen as a deterrent; however, foreign direct investment activity in the energy sector was virtually limited to the semi-autonomous region of Kurdistan. Investments were either wholly-owned or joint-venture enterprises. Implications to other post conflict countries, using Kuwait and Nigeria as illustrative examples, are presented and recommendations made. Keywords: Foreign direct investment; Iraq; post-conflict country; energy JEL Classifications: F21; F23; O53; P28